Models of pedagogical coach and their incidence in coaching proposals for basic education in Mexico - Reséndiz Melgar, Norma Nélida (Avances en Supervisión Educativa, 2020)
This text is about different models of educational coaching that have had a presence in the history of basic education in Mexico, according to constituent interests of the knowledge of Habermas as criteria of classification. The first content is the difference between coaching with other similar terms, such as mentoring, training or management, then the characteristics of this coaching are pointed out and a notion about it is approached. Next, different models of advice are presented according to the interests considered. These models are analyzed according to the conceptions of knowledge, teaching, learning and educational change that they propose. Finally, some comments are included about aspects to consider improving coaching in the Mexican context what was discussed.
Keywords: coaching school; technical assistance at school; teacher development; basic education; educational models